2007
DOI: 10.1007/s00384-007-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selective defunctioning stoma after low anterior resection for rectal cancer

Abstract: Finding lower clinical leakage rate in a probable higher risk group and better outcome when a leak occurs in our study constituted strong evidence of the effectiveness of a DS. Selective use of a DS based on subjective assessment at the time of surgery could not allow experienced surgeons to perform single-stage procedure safely. Construction of a DS seems useful for patients with distal rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
1
25
1
6
Order By: Relevance
“…Possible factors contributing to an increased leakage rate include the reduced blood supply of the anorectal remnant and the large pelvic space after TME, which may predispose a patient to fluid accumulation and pelvic infection [34] . Symptomatic anastomotic leakage is the most feared complication and [22] 2008 256 136 120 LAR 3 12 0 2 Gong et al [23] 2012 62 36 26 uLAR 0 5 0 2 Karahasanoglu et al [24] 2011 77 23 54 LAR 0 3 --Lefebure et al [25] 2008 132 42 90 LAR 3 10 1 5 Ma et al [26] 2013 56 30 26 LAR 2 7 0 5 Matthiessen et al [27] 2007 [29] 2013 836 246 590 uLAR 1 22 --Shiomi et al [30] inherent consequences [38] . Nonetheless, the value of a protective stoma has been the subject of controversy for many years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible factors contributing to an increased leakage rate include the reduced blood supply of the anorectal remnant and the large pelvic space after TME, which may predispose a patient to fluid accumulation and pelvic infection [34] . Symptomatic anastomotic leakage is the most feared complication and [22] 2008 256 136 120 LAR 3 12 0 2 Gong et al [23] 2012 62 36 26 uLAR 0 5 0 2 Karahasanoglu et al [24] 2011 77 23 54 LAR 0 3 --Lefebure et al [25] 2008 132 42 90 LAR 3 10 1 5 Ma et al [26] 2013 56 30 26 LAR 2 7 0 5 Matthiessen et al [27] 2007 [29] 2013 836 246 590 uLAR 1 22 --Shiomi et al [30] inherent consequences [38] . Nonetheless, the value of a protective stoma has been the subject of controversy for many years.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated 18 potential candidate studies in the full text, 7 of which were not published in English. Finally, 11 studies [21][22][23][24][25][26][27][28][29][30][31] were included in this meta-analysis, all of which were published between 2007 and 2014. The flow chart of study selection is presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As some surgeons believe that "the lesser anastomotic site fecal contamination, the lesser chance of anastomotic site leakage", using diverting ileostomy or colostomy would be a constant part of their low or ultralow anterior resection [1][2][3][4][5][6][7][8]; although several recent studies have not confirmed this idea, and only persisted on less complication of the possible leakage such as the pelvic sepsis [11,19] or and less operational needs for further possible leakages [23,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Diverting stomas for low and ultralow rectal anastomosis are being constructed routinely in some colorectal centers [1][2][3][4][5][6][7][8] based on crediting the fact that creating route diverting stomas, and thereby making a space from the anastomosis, lowers the anastomotic leakage incidence; whereas, some other centers have shown the reverse [9][10][11][12][13]. Furthermore, the stoma itself would increase the morbidity in construction time, life period, and closure time, which also in its place needs reoperation and hospitalization, and so has its own morbidity and mortality [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Esses fatos não são iguais, mas estão de conformidade com o que se observa na literatura 82,84,92,93 , e que tem sido a razão da tendência em aconselhar a derivação intestinal protetora nas situações em que o procedimento é a ETM com anastomose cólon-anal 84,92,94,95 , opinião não compartilhada por todos 51,96 para ser deixada como opção em situações especiais 97 , com todos os ônus inerentes aos cuidados exigidos, principalmente os relacionados ao planejamento da confecção do estoma, e às complicações não desprezíveis que decorrem da reconstrução do trânsito intestinal [98][99][100][101] , além de outros transtornos vinculados à colostomia que abalam a qualidade de vida desses pacientes 102,103 .…”
Section: B Retossigmoidectomia Anterior Com Etmunclassified